Global research landscape and hotspots for ferroptosis in glioma: A comprehensive bibliometric and visual analysis - Xinyue Zheng; Mengyao Diao; Shan Tong; Shuo Yang; Jing Lin; Shenghua Zhuo; Ting Wang; Jian Dai; Shenbo Chen; Kai Wang (Heliyon)
Studying ferroptosis is crucial for understanding the mechanisms underlying the onset and progression of glioblastoma, identifying therapeutic targets, and improving prognosis assessment and diagnostic methods. While recent research has explored the link between ferroptosis and glioblastoma, there is a lack of comprehensive bibliometric analyses specifically addressing this relationship and its connection to glioblastoma. To address this gap, we conducted a thorough analysis of 225 relevant articles on glioma and ferroptosis obtained from the Web of Science database covering the period from 2012 to 2023, employing rigorous exclusion criteria. Visual and statistical analyses were performed using CiteSpace, VOSviewer, R Studio Plotting, and Scimago Graphica Beta. Our findings revealed a significant exponential growth in the number of studies during the last decade. China, the United States, and Germany made the most substantial contributions to research in this field, collectively accounting for 76.2 % of the total research output. Notably, Central South University, Shandong University, and Zhejiang University emerged as leaders in both literature production and research collaboration. Frontiers in Oncology stood out as the most prolific journal, encompassing a wide array of topics from molecular mechanisms to potential therapeutic strategies. Visual keyword analysis highlighted ''tumor biology'' ''cell death mechanisms'' and ''gene expression and metabolic processes'' as central themes in the research network. This study offers a comprehensive visual perspective on the global publication landscape of ferroptosis in glioma, providing valuable insights for researchers seeking to understand the current state of the field and identify potential directions for future studies.